Gestão industrial: aplicação de TPM em uma linha de produção do segmento alimentício - Marques, Gustavo Henrique (2019)
The search for continuous improvement through the optimization of resources and implementation of new management philosophies in the food industries is fundamental for them to remain competitive in the market. Thus, this study sought to identify and analyze the implementation of the TPM (Total Productive Maintenance) management philosophy in a production line of greasy products and according to the analysis of the results of the implementation, propose improvements in the manufacturing environment. The study was characterized as applied as to its nature, and from the point of view of approaching the problem as quantitative. As for the objectives classified as explanatory, assuming as the auxiliary technical procedures the bibliographic research and case study. As a result, it was possible to analyze the main bottlenecks of the industrial line and the productive gain with the adequacy of operating procedures. The use of line efficiency indicators such as OEE, OPE and IUA was implemented from the deployment of the organization's strategic guidelines. It is concluded with this study that the proposed objective of this work was successfully achieved. It was ensured the application of TPM tools in the industrial food production line seeking the optimization of resources, processes and understanding of the applied management philosophy. It could be observed that the improvement team that was managed by the production team, aiming at reducing product losses, also contributed to the formation of a solid culture focused on preventive maintenance, collaborating not only to solve a specific problem, but also by strengthening the process of TPM implementation in the organization.